Optimalisasi Komunikasi Efektif Sebagai Sarana Ekspresi Diri dan Pemahaman Antar Pribadi Pada Generasi Z - Rajesh Prettypal Singh; Yoanita Alexandra; Boby Arinto; Wanda Gema P.A. Hidayat (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service initiative aims to enhance the understanding and effective communication skills of Generation Z students at SMA Ekayana Ehippasiko BSD Tangerang. The program is motivated by the declining interpersonal communication abilities among adolescents due to a high dependency on digital technology, which frequently leads to miscommunication and negative stigmatization. The workshop was conducted on Wednesday, May 6th, 2026, by a collaborative team of lecturers, students, and practitioners from the Management study program of Universitas Multimedia Nusantara. The implementation methodology encompassed lecturing sessions, question and answer periods, and interactive workshops. The results indicate a significant increase in students' awareness regarding the importance of assertive communication styles, an improved comprehension of information pollution (comprising misinformation, disinformation, and malinformation), and the strategic utilization of storytelling as a medium for positive self-expression. The study concludes that sustainable communication literacy is essential to assist students in navigating social interactions within the digital era in a healthier and more public-oriented manner.